Software Engineering Aspects of Continuous Development and New Paradigms of Software Production and Deployment : Second International Workshop, DEVOPS 2019, Château de Villebrumier, France, May 6–8, 2019, Revised Selected Papers /: Second International Workshop, DEVOPS 2019, Château de Villebrumier, France, May 6–8, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available